Perancangan PERANCANGAN SISTEM LAPORAN KEUANGAN DAN PERPAJAKAN SEDERHANA BERBASIS EXCEL UNTUK EFISIENSI WAKTU PENGELOLAAN DATA PADA UMKM BAKULAN ICUY: PERANCANGAN SISTEM LAPORAN KEUANGAN DAN PERPAJAKAN SEDERHANA BERBASIS EXCEL UNTUK EFISIENSI WAKTU PENGELOLAAN DATA PADA UMKM BAKULAN ICUY - Dwi Ratna Febriani (LP2M Politeknik Jambi, 2026)
Automation of the Microsoft Excel-based financial and tax reporting system at Bakulan Icuy MSME is designed to overcome the constraints of manual recording and time inefficiency. Using a descriptive qualitative method, this research produces an integrated system that includes General Journal modules, Income Statements, and Balance Sheets in accordance with SAK EMKM, as well as 0.5% Final Income Tax calculations. The results indicate that the implementation of this system significantly improves data accuracy and financial management time efficiency. Through this system, Bakulan Icuy MSME can generate reliable financial information to support tax compliance and more effective business decision-making.